Reception, Accommodation, and Farewell of the Sultan Abdülaziz in Britain - Emel Demir Görür (Tarih Dergisi)
With the exception of military campaigns in Ottoman history, the only Sultan who traveled to foreign countries and the only caliph who went to Christian countries as an ally was Sultan Abdülaziz. One of the most important stops during Sultan’s journey to Europe in 1867 was Britain. He visited many institutions here and stayed for more than ten days, participated in banquets and balls, was given in his honour and hosted many influential people and institutions at the reception he gave. Sultan’s journey to Europe, the British leg of his travel in particular, aroused great interest in the British press, and liberal, conservative, and satirical newspapers kept a close eye on Sultan. There were page-by-page news about the balls given in the name of the Sultan, the entertainments organised, the apparel and attitudes of the Sultan and his entourage, and what they ate and drank. Accordingly, this study aims to convey the reflections of this journey in British liberal, conservative, and satirical newspapers and to exhibit the attitudes of dissidents and supporters towards the journey together with their impressions and reflections on the British front. The perception of Sultan and Islam that existed in Britain and changed during the journey will also be revealed.